The reciprocal changes in dominant species with complete metabolic functions explain the decoupling phenomenon of microbial taxonomic and functional composition in a grassland - Liu, Huaiqiang; Li, Frank Yonghong; Liu, Jiayue; Shi, Chunjun; Tang, Kuanyan; Yang, Qianhui; Liu, Yu; Fu, Qiang; Gao, Xiaotian; Wang, Ning; Guo, Wei (Frontiers in Microbiology, 2023)
The decoupling of microbial functional and taxonomic components refers to the phenomenon that a drastic change in microbial taxonomic composition lead to no or only a gentle change in functional composition. Although many studies have identified this phenomenon, the mechanisms underlying it are still unclear. Here we demonstrate, using metagenomics data from a steppe grassland soil under different grazing and phosphorus addition treatments, that there is no "decoupling" in the variation of taxonomic and metabolic functional composition of the microbial community within functional groups at species level. In contrast, the high consistency and complementarity between the abundance and functional gene diversity of two dominant species made metabolic functions unaffected by grazing and phosphorus addition. This complementarity between the two dominant species shapes a bistability pattern that differs from functional redundancy in that only two species cannot form observable redundancy in a large microbial community. In other words, the "monopoly" of metabolic functions by the two most abundant species leads to the disappearance of functional redundancy. Our findings imply that for soil microbial communities, the impact of species identity on metabolic functions is much greater than that of species diversity, and it is more important to monitor the dynamics of key dominant microorganisms for accurately predicting the changes in the metabolic functions of the ecosystems.